Jews, punk and the Holocaust: From the Velvet Underground to the Ramones: The Jewish-American story - Stratton, Jon (Cambridge University Press, 2005)
Punk is usually thought of as a radical reaction to local circumstances. This article argues that, while this may be the case, punk’s celebration of nihilism should also be understood as an expression of the acknowledgement of the cultural trauma that was, in the late 1970s, becoming known as the Holocaust. This article identifies the disproportionate number of Jews who helped in the development of the American punk phenomenon through the late 1960s and 1970s. However, the effects of the impact of the cultural trauma of the Holocaust were not confined to Jews. The shock that apparently civilised Europeans could engage in genocidal acts against groups of people wholly or partially thought of by most Europeans as European undermined the certainties of post-Enlightenment modernity and contributed fundamentally to the sense of unsettlement of morals and ethics which characterises the experience of postmodernity. Punk marks a critical cultural moment in that transformation. In this article the focus is on punk in the United States.